Building Resilient Data Ingestion Pipelines for Third-Party Vendor Data Integration - Paulraj, Balachandar (Journal for Research in Applied Sciences and Biotechnology, 2022)
In this report, the author provides a review of the design and operation of the resilient data ingestion architecture with a particular emphasis on the issues associated with third-party data vendor integration. As more and more companies have made information a principal factor in their business strategies, it has become equally imperative to obtain external data in a coherent manner. This paper describes ways of handling Enhanced Data Ingestion Reliability Efficiency and Adaptability and other challenges such as Data quality Error Handling and Scalability.